2013
DOI: 10.5539/jas.v5n10p108
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Households Vulnerability to Climate Change in Swaziland: A Case of Mpolonjeni Area Development Programme (ADP)

Abstract: This study investigated household vulnerability to climate change and the factors affecting vulnerability of the households at Mpolonjeni Area Development Programme in Swaziland. Primary data were collected through personal interviews from 323 randomly sampled households. The household vulnerability index was used to establish household vulnerability and the multinomial logistic regression model was used to identify the factors affecting household vulnerability. The results show that 39.6% of the households we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 5 publications
4
19
0
Order By: Relevance
“…Only two studies presented differences in time scale in their assessment using primary information from census data. These were from Ghana (Dasgupta and Baschieri 2010) and Swaziland (Nkondze et al 2013) and concluded that the dynamic nature of vulnerability is understudied. According to Singh et al (2017), lack of attention paid to temporal scales during vulnerability assessments has implications on reporting differences in vulnerability over different timescales to understand dynamism of vulnerability, especially in the context of seasonality and rural livelihoods in Africa.…”
Section: Types Of Methods Used In the Design And Analysis Of Vaosasmentioning
confidence: 99%
“…Only two studies presented differences in time scale in their assessment using primary information from census data. These were from Ghana (Dasgupta and Baschieri 2010) and Swaziland (Nkondze et al 2013) and concluded that the dynamic nature of vulnerability is understudied. According to Singh et al (2017), lack of attention paid to temporal scales during vulnerability assessments has implications on reporting differences in vulnerability over different timescales to understand dynamism of vulnerability, especially in the context of seasonality and rural livelihoods in Africa.…”
Section: Types Of Methods Used In the Design And Analysis Of Vaosasmentioning
confidence: 99%
“…Households with large number of dependents often direct larger proportion of their resources (finance, time) towards the welfare of the household members [5,37,43,59], leaving them with little resources to access additional and or alternative livelihood options to enhance their capacity against the impact of climate change and variability. High level of literacy reduces vulnerability by increasing the ability to access and understand climate [11] events and impact-related warning, adaption and recovery information [7,41].…”
Section: Social Vulnerability To Climate Change: Determining Factors mentioning
confidence: 99%
“…Household size is found to influence vulnerability (e.g. [5,37,43,59]), while it is also associated with reducing vulnerability particularly in agricultural economies where large family size is preferred for improving economic condition [31] and for labour supply. However, considering the context of the study area and the respondents, it was realized that though the many members of the household do contribute labour as unpaid family workers, most these are dependents who do not attract additional external income to the household thereby, increasing the household's vulnerability in the long run.…”
Section: Indicator Validitymentioning
confidence: 99%
“…Other studies have been conducted to quantify vulnerability at household and national levels [22]- [24]. Most national levels vulnerability studies consisted at comparing different countries to identify hotspots where development actions are most needed.…”
Section: The Indicator Approach Of Vulnerability Assessmentmentioning
confidence: 99%
“…The reason supporting the choice of this indicator is that the poor are often discriminated against access to resources rendering them intrinsically more vulnerable. More recently, [24] used an indicator approach to investigate household vulnerability to climate change and identify the factors affecting vulnerability of households in Swaziland. This approach permitted to classify households based on their level of vulnerability and to formulate differentiated policy actions to address households' needs.…”
Section: The Indicator Approach Of Vulnerability Assessmentmentioning
confidence: 99%